2000
DOI: 10.1590/s0041-87812000000300003
|View full text |Cite
|
Sign up to set email alerts
|

Age related changes in the elastic fiber system of the interfoveolar ligament

Abstract: In order to evaluate age related changes of the elastic fiber system in the interfoveolar ligament, we studied the deep inguinal ring from 33 male cadavers aged from stillborn to 76 years. Selective and alternated staining methods for elastic fibers were performed to differentiate oxytalan, elaunin, and mature elastic fibers. We confirmed quantitative changes of the elastic fiber system with aging. There was a significant and progressive reduction of the oxytalan fibers (responsible for tissue resistance) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
3
17
1
5
Order By: Relevance
“…In the present work, the linear density of elaunin fibers and elastic fibers was increased in the elderly group compared to the young group, and oxytalan fibers was decreased in the elderly group compared to the young group. Similar results were described by [44,45] , who found that during aging, there was a decrease in oxytalan fibers and an increase mature elaunin and elastic fibers. Furthermore, elastin was thicker and more fragmented in older people, and there was a greater deposition of calcium in the amorphous material.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present work, the linear density of elaunin fibers and elastic fibers was increased in the elderly group compared to the young group, and oxytalan fibers was decreased in the elderly group compared to the young group. Similar results were described by [44,45] , who found that during aging, there was a decrease in oxytalan fibers and an increase mature elaunin and elastic fibers. Furthermore, elastin was thicker and more fragmented in older people, and there was a greater deposition of calcium in the amorphous material.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, study of the interspinous ligament during aging found the disappearance of oxytalan fibers [48] , which is in agreement with our results. In addition to our study, authors suggested that aging is accompanied by a significant and progressive reduction in oxytalan fibers and significant increases in mature elaunin and elastic fibers in the interfoveolar ligament [44] . Elaunin fibers play an intermediary role between oxytalan fibers and mature elastic fibers, providing functional adaptation in different tissues.…”
Section: Discussionsupporting
confidence: 79%
“…elastic fibers and reduction in the amount of oxytalan fibers. These structural changes can explain the high incidence of groin hernias in patients after the fifth decade (Rodrigues Jr et al 6 , Quintas et al 7 ). With aging there was a decreased collagen content in the fascias, as well as decreased extractability of collagen with pepsin (Pans et al 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigues Junior et al 6 and Quintas et al 7 have shown structural and quanti-tative age-related changes in the TF elastic fibers. These results indicate clearly that there is a morphological correlate to the loss of tensile resistance and elasticity of the TF with aging, and this loss can explain the high incidence of inguinal hernia in patients after the fifth decade of life.…”
Section: Introductionmentioning
confidence: 98%
“…Research by our group has shown age-related structural changes (breaching and wrapping) in the elastic fibers, with ultrastructural studies showing a large decrease in the quantity of microfibril component ( Rodrigues Jr. et al., 1990;Quintas et al, 2000). Some studies have shown reduced amounts of collagen in the fascia transversalis of patients with direct inguinal hernia compared to those with indirect hernia, suggesting that the development of some hernias might be influenced by disturbances in collagen metabolism (Pans et al, 2001;Rodrigues Jr et al, 2002).…”
Section: Introductionmentioning
confidence: 93%